Conventional and atom transfer radical copolymerization of phenoxycarbonylmethyl methacrylate-styrene and thermal behavior of their copolymers - Barim, G.; Demirelli, K.; Coskun, M. (Budapest Univ Technol & Econ, 2007)
The atom transfer radical polymerization (ATRP) of phenoxycarbonylmethyl methacrylate (PCMMA) with styrene (St) were performed in bulk at 110 C in the presence of ethyl 2-bromoacetate, cuprous(I) bromide (CuBr), and N,N,N',N '',N ''-pentamethyldiethyltriamine. Also, a series conventional free-radical polymerization (CFRP) of PCMMA and styrene were carried out in the presence of 2,2'-azobisisobutyronitrile in 1,4-dioxane solvent at 60 C. The structure of homo and copolymers was characterized by IR, H-1 and C-13-NMR techniques. The composition of the copolymers was calculated by H-1-NMR spectra. The average-molecular weight of the copolymers were investigated by Gel Permeation Chromatography (GPC). For copolymerization system, their monomer reactivity ratios were obtained by using both Kelen-Tudos and Fineman-Ross equations. Thermal analysis measurements of homo- and copolymers prepared CFRP and ATRP methods were measured by TGA-50 and DSC-50. Blends of poly(PCMMA) and poly(St) obtained via ATRP method have been prepared by casting films from dichlorormethane solution. The blends were characterized by differential scanning calorimetry. The initial decomposition temperatures of the resulting copolymers increased with increasing mole fraction of St.
Keywords: polymer synthesis; molecular engineering; polymer composites; thermal properties